1. The problem statement, all variables and given/known data: In the image above, the toy consists of two identical mass hanging from a peg. we take the zero potential energy at the pivot. 2. Relevant equations: http://www.physicsmynd.com/?p=1172 3. The attempt at a solution Since the potential energy is zero at the pivot, and the potential energy is defined by U(θ)=mgh, I had: U(θ)= mg(- l*cos(α+θ)- l*cos(α-θ)) but the solution is: U(θ)= mg(L*cos(θ) - l*cos(α+θ)) +mg(L*cos(θ) - l*cos(α-θ)) So my question is,what is wrong with my answer, and why?